Microplastics Depuration Using Seawater In Asiatic Hard Clams (Meretrix) In The Waters Of The Jenelata River, Gowa - Yuliati, Yuliati; Hasriwiani Habo Abbas; Arni Rizqiani Rusydi; Alfina Baharuddin; Nur Ulmy Mahmud; Sumiaty, Sumiaty; Safruddin, Safruddin (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2025)
Depuration is an effort to reduce/eliminate contamination, including microplastics, using a water circulation system. This study aims to determine the effective depuration time to reduce the microplastic content in Asiatic hard clams (Meretrix). This study used a quantitative approach with an experimental research design and a completely randomized design. There are 450 clams used as an experimental animal where the treatment consisted of four depuration times, namely 1, 2, 3, and 4 days with three repetitions of each treatment, while the control clams were without depuration. Analysis of variance (ANOVA) was used to see the effect of depuration treatment on the microplastic content. If the effect of the treatment was significantly different, then the Post Hoc Test was continued to determine the differences between treatments. The results showed that Asiatic hard clams (Meretrix) obtained from the mouth of the Jenelata River, Gowa, were contaminated with microplastics ranging from 0.6 to 8.1 MPs/clam and an average of 3.96 MPs/clam. Depuration time significantly affected the microplastic content in clams' depuration effectiveness. There is a tendency for a longer depuration time to decrease microplastic content in clams. The adequate depuration time to reduce the microplastic content in Asiatic hard clams (Meretrix) was 3 and 4 days. Based on the findings of this study, it is recommended that further research be conducted to explore methods for reducing microplastics using natural materials.